A Microscale Perovskite as Single Component Broadband Phosphor for Downconversion White‐Light‐Emitting Devices. Issue 12 (26th September 2016) - Yuan, Zhao; Zhou, Chenkun; Messier, Joshua; Tian, Yu; Shu, Yu; Wang, Jamie; Xin, Yan; Ma, Biwu
Abstract : A microscale corrugated halide perovskite with broadband emission is prepared by a facile one‐pot synthsis at room temperature. A UV‐pumped white‐light‐emitting diode with CIE coordinates of (0.30, 0.42) is fabricated by using this microscale perovskite as a single component downconversion phosphor.